2008
DOI: 10.1007/s00203-008-0374-6
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of soil fungal communities of Cerrado and its closely surrounding agriculture fields

Abstract: Cerrado is a savanna-like region that covers a large area of Brazil. Despite its biological importance, the Cerrado has been the focus of few microbial diversity studies. A molecular approach was chosen to characterize the soil fungal communities in four areas of the Cerrado biome: a native Cerrado, a riverbank forest, an area converted to a soybean plantation, and an area converted to pasture. Global diversity of fungal communities in each area was assessed through Ribosomal intergenic spacer analysis which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 49 publications
7
37
2
1
Order By: Relevance
“…In tropical ecosystems, the responses of soil fungal biodiversity to land-use change are only beginning to be explored, and responsiveness has been shown in some cases (for example, Fracetto et al, 2013) but not in others (for example, Leal et al, 2009). Fungal communities can be structured by nutrient availability (Rousk et al, 2010) and plant community composition (Carney and Matson, 2006;Peay et al, 2013), suggesting that shifts in soil fungal communities in response to land-use change (Castro et al, 2008;Fracetto et al, 2013) could result from alterations in soil properties and/or plant communities. However, the relative strength of these factors in determining fungal community composition in tropical systems has not been examined.…”
mentioning
confidence: 99%
“…In tropical ecosystems, the responses of soil fungal biodiversity to land-use change are only beginning to be explored, and responsiveness has been shown in some cases (for example, Fracetto et al, 2013) but not in others (for example, Leal et al, 2009). Fungal communities can be structured by nutrient availability (Rousk et al, 2010) and plant community composition (Carney and Matson, 2006;Peay et al, 2013), suggesting that shifts in soil fungal communities in response to land-use change (Castro et al, 2008;Fracetto et al, 2013) could result from alterations in soil properties and/or plant communities. However, the relative strength of these factors in determining fungal community composition in tropical systems has not been examined.…”
mentioning
confidence: 99%
“…Studies on the diversity, distributional patterns and faunistic composition of the Cerrado are urgently needed, since large areas in this domain are being transformed into crops, pastures (Camargo & Becker 1999, Castro et al 2008, Carrijo et al 2009) and forests of exotic trees, mainly eucalypts (Oliveira 1998). Evidences suggest that habitat alteration may affect local faunas of pollinating insects (e. g. Aizen & Feinsinger 1994, Steffan-Dewenter et al 2002 and that these effects can be more pronounced in tropical areas (Ricketts et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies on fungal community in tropical areas showed that forest-to-agriculture conversion can alters the abundance of members in soil fungal microbial communities [31,32]. In Cerrado, Castro et al [9] showed decrease in soil fungal microbial community diversity after soybean cultivation. Bresolin et al [11] studied soil fungal microbial communities in native Cerrado and no-tillage soybean monoculture area, and their results revealed different alterations in soil fungal microbial communities due to soil cover changes (fallow vs. growth period) and crop development.…”
Section: Number Of Phylotypes In Eachmentioning
confidence: 99%
“…The physical, chemical and biological attributes of the soil are affected by several conditions related to the type of soil preparation used in each management system; the effects on these attributes are dependent on the intensity of soil disturbance, traffic of farm tractors, type of equipment used, management of plant waste, and moisture conditions in the soil at the time of tillage [8]. Despite previous findings in areas of the Cerrado biome [9][10][11], there is a lack of information about the impact of soil agricultural management on the fungal microbial community in Cerrado areas.…”
Section: Introductionmentioning
confidence: 99%